Educational robotics - See, Tian Bao. (2010)
In this project, the objective is to build a robotic arm from scratch and design an easy to use user interface for students to understand the Denavit-Hartenberg algorithm. The four kinematic parameters, (joint angle), d (joint distance), a (link length), (link twist angle) can be obtained after applying the Denavit-Hartenberg algorithm. With the four kinematic parameters, the final transformation matrix which maps the coordinates of the robotic arm from the end-effector to the base can also be found. With the transformation matrix, students will be able to solve for the forward kinematics problem which is to find the coordinates of the end-effector with respect to the base when the rotation angle of indvidiual motor are known. They will also be able to solve for the inverse kinematics problem which is to find the corresponding angles that the individual motors need to rotate when the coordinates of the end-effector are known.